Cold plasma application to fresh green leafy vegetables: impact on microbiology and product quality - Özdemir, Emel; Başaran, Pervin; Kartal, Sehban; Akan, Tamer (Wiley, 2023)
Fresh green leafy vegetables (FGLVs) are consumed either garden-fresh or by going through very few simple processing steps. For this reason, foodborne diseases that come with the consumption of fresh products in many countries have prioritized the development of new and reliable technologies to reduce food-related epidemics. Cold plasma (CP) is considered one of the sustainable and green processing approaches that inactivate target microorganisms without causing a significant temperature increase during processing. This review presents an overview of recent developments regarding the commercialization potential of CP-treated FGLVs, focusing on specific areas such as microbial inactivation and the influence of CP on product quality. The effect of CP differs according to the power of the plasma, frequency, gas flow rate, application time, ionizing gases composition, the distance between the electrodes and pressure, as well as the characteristics of the product. As well as microbial decontamination, CP offers significant potential for increasing the shelf life of perishable and short-shelf-life products. In addition, organizations actively involved in CP research and development and patent applications (2016–2022) have also been analyzed.
Keywords: cold plasmas; microbial decontamination; fresh green leafy vegetables; vegetables